Accurate flowrate measurement for chilled water plant - Reinaldo, Gian (2017)
Chilled water cooling system accounts for 30%-50% of total building energy consumption of large building. To monitor the operating status of the system and evaluate the energy consumption, an accurate Measurement and Verification (M&V) system is required. Flow-rate is an essential parameter for evaluating energy consumption. To accurately measure the flow-rate, enough straight pipes are usually required to get the stable flow profile. However, due to the limited space and complex piping system in the plant room, it is usually impossible to get long enough straight pipes where flow meters are installed. In this project, an M&V system in an actual chilled water plant with a bypass pipe installed will be used to test the performance of flow meters with 0D configuration under different flow-rate ranges. I will be testing the flow-rate of four different type of flow meters (ABB standard , ABB 0D , Siemens standard , Siemens 0D) in six different types of flow-rate in the real time chilled water plant at Techno Plaza, Nanyang Technological University. From the results acquired, I will be analyzing and studying the impacts of four different flow meters under different flow-rates (low to high). Besides measuring and verification on the flow rates data, I will also be analyzing the pressure differences across the flow meters in the chilled water plant piping system. Finally, I will conclude my studies and findings with some recommendations and challenges faced along the way.